'You cannot be serious!': McEnroe's Ghost causes a scene at the Wimbledon Lawn Tennis Museum. Issue 1 (15th December 2012) - Chittenden, Tara
Exhibition designers are now encountering unprecedented opportunities to merge the virtual and the real in the creation of scenes. I argue that there is a clear need to examine how the 'technospectacle' is transforming the visual and material regimes of scene design in a museum context. Bringing together the technique of Pepper's Ghost with new projection and filming technology, the Wimbledon Lawn Tennis Museum introduces a 3D life-sized ghost of John McEnroe into a reconstruction of the 1980s Dressing Room. In this article I investigate the intersection of technology and tangible reconstruction in 'McEnroe's Ghost'. In my analysis I question not only how different arrangements of time and space constitute the scene as encountered by visitors but how these arrangements serve to create a real sense of presence in the experience of viewing the virtual body. I conclude that such technologically augmented scenes suggest rich possibilities to extend scene design visually, conceptually and dramatically, via new intersections of projection and performance.